Spinning waveforms of scalar radiation in quadratic modified gravity - Adam Falkowski; Panagiotis Marinellis (European Physical Journal C: Particles and Fields)
Abstract We study scalar–tensor gravitational theories using on-shell amplitude methods. We focus on theories with gravity coupled to a massless scalar via the Gauss–Bonnet and Chern–Simons terms. In this framework, we calculate the waveforms for classical scalar radiation emitted in scattering of macroscopic objects, including spin effects. To this end, we use the Kosower–Maybee–O’Connell formalism, with the 5-particle amplitude for scalar emission in matter scattering calculated at tree level using the unitarity-factorization bootstrap techniques. We also discuss in detail the dependence of that amplitude on the contact terms of the intermediate 4-particle scalar-graviton-matter amplitude. Finally, we discuss the conditions for resolvability of classical scalar radiation.